Pengembangan Perangkat Lunak Generate File Untuk Migrasi Data EPSBED Ke Format Table Feeder PDDIKTI - Pranatawijaya, Viktor Handrianus (STMIK Palangkaraya, 2016)
Based on SK-03, DIKTI requires all universities provide a report on each semester that corresponding to the report format named EPSBED. EPSBED report is one indicator of a study program at the college as it is called active and abiding by the principle. The reporting of data is conducted every semester and should be reported such as the data of students, the data of subjects, the data of lectures, the value of relocation, the lectures activities of students, and the status of students. The research MADE data migration software used library research and observation. Furthermore, processing the EPSBED data to excel in accordance with the template of PDDIKTI Feeder preceded by mapping EPSBED table with PDDKTI Feeder table.Determine the functionality of the software, made the design and implemented in the programming language of PHP. The software testing was conducted using EPSBED data of Informatics Engineering Department Palangka Raya University. The software developed produce excel file containing the data of students (profile and status), the data of subjects and the assessment, the data of lectures (class lectures, students KRS, lecturer, subjects, and students grade), and the lectures activities of students. Data Migration Software to PDDIKTI Feeder to assist and facilitate the reporting of PDPT UPR. In other words, Data Migration Software to PDDIKTI Feeder can be a model and reference in the subsequent development, in which an existing excel file with the help of Web Service PDDIKTI Feeder can be inputted the data into the feeder DIKTI so that it can be displayed on Forlap DIKTI.